The dilemma of naval modernisation in East Asia - Yoon, Sukjoon (2012)
Recent maritime conflicts and disputes are occurring amid the increasingly rapid modernisation of naval power by East Asian states. The consequences of this modernisation are as still uncertain, but will it lead to a naval arms race or to enhanced naval cooperation?